Pengembangan E-Module Berbasis Problem Based Learning Mata Pelajaran Ekonomi Kelas X SMA Negeri 1 Percut Sei Tuan Tahun Ajaran 2018/2019 - Pebri Hastuti; Roza Thohiri; Yanti Panggabean (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
This study aims to: (1) produce appropriate e-modules as problem based learning media for class X (2) determine the feasibility of e-modules by referring to the teaching material criteria specified by the Ministry of National Education, (3) knowing the evaluation results Class X students after using the e-module based on problem based learning. This research is a type of research development of R&D (Research and Development) with reference to the ADDIE development model including Analysis, Design, Development, Implementation, Evaluation. The subjects of this study include 2 media expert lecturers, 1 lecturer and 1 subject matter expert teacher, and class X students of SMA Negeri 1 Percut Sei Tuan. The object of this study is the e-module learning instruments used to assess the feasibility of e-modules include the eligibility assessment sheet by material experts, the eligibility assessment sheet by media experts, and student questionnaire responses to the use of e-modules. The results showed (1) e-module learning developed into E-Module Concept Management Based On Problem Based Learning for class X students, (2) the e-module developed was declared to be feasible with the average score obtained by material experts at 3.46 , media experts amounted to 3.19, and by student responses amounted to 3.19 so that the feasibility of the developed e-module was included in the "Very Good" category, (2) the results of student learning evaluations obtained a percentage of 85.71% in the high success criteria category.